Effect of sinusoidal function on backpropagation learning - Karimi, B.; Ashenayi, K.; Seyed, T.B. (Association for Computing Machinery, 1992)
The backpropagation method is modified by replacing sigmoid function by sinusoidal function. The leaving law is also modified. The modified procedure shows great improvement over the original BP in terms of the number of neurons and the learning time. © 1992 IEEE.
Keywords: Backpropagation; Backpropagation learning; Circuit simulation; Learning time; Sigmoid function; Sinusoidal functions; Software engineering; dept.csc

Selective detection of linear features in geological remote sensing data - Parikh, Jo Ann; DaPonte, John S.; DiNicola, Emily G.; Pedersen, Robert A. (SPIE, 1992)
One of the major problems in the development of computer- A ssisted systems for geologic mapping is how to individualize the system to meet user needs. Ideally, the system should be responsive to specifications of desired types of output structures. Also the system should be able to incorporate the user's knowledge of regional characteristics into the feature extraction/selection and classification components. Automatic techniques for classification of remote sensing data typically require relatively large, labeled training sets which are well-organized with respect to the desired mapping between input and output patterns. The present paper focuses on the feature extraction/selection component of the system. Kohonen self-organizing feature maps in conjunction with image processing procedures for linear feature extraction are used for explorative data analysis, feature selection, and construction of exemplar patterns. The results of training Kohonen feature maps with different pattern sets and different feature combinations provide insight into the nature of pattern relationships which enables the user to develop sets of positive and negative training patterns for the classification component. © 1992 SPIE. All rights reserved.
Keywords: Automatic technique; Classification (of information); Conformal mapping; Data mining; Explorative data analysis; Extraction; Feature extraction; Feature extraction/selection; Image processing; Kohonen self-organizing feature map; Linear feature extraction; Regional characteristics; Remote sensing; Remote sensing data; Selective detection; Self organizing maps; dept.csc